Histopathological Changes of Liver Observed in Paediatric Patients Presenting with Choledochal Cyst: A Cross-sectional Study in a Tertiary Care Hospital, Kolkata, India - Swagata Mistry; Ruplekha Mitra Mustaphi; Saugata Kumar Bhattacharya; Seema Mondal (National Journal of Laboratory Medicine)
Introduction: Choledochal cyst is an uncommon congenital anomaly of the biliary tract, with a higher incidence seen in Asia. It is commonly associated with Pancreaticobiliary Malunion (PBMU). It is believed to be caused by two factors: weakness of the wall and obstruction distal to it. Choledochal cysts can be roughly classified into two types according to the shape of the common bile duct: cystic dilatation and fusiform dilatation. They may be intrahepatic, extrahepatic, or both. Recognition and management of choledochal cyst disease are important due to the risk of developing cholangiocarcinoma and various pathological changes in liver tissue. Aim: To investigate hepatocellular changes, with particular attention to fibrosis, in paediatric patients with choledochal cyst. Materials and Methods: A descriptive cross-sectional study was carried out in the Outpatient Department (OPD), Institute of Postgraduate Medical Education and Research, SSKM Hospital, Kolkata, West Bengal, India, from October 2017 to September 2019. A total of 48 cases from both sexes in the paediatric age group were collected over a period of one year and eleven months. After obtaining clinical histories, histopathological examinations were performed on all cases to diagnose choledochal cyst and to assess the associated hepatocellular abnormalities. Routine Haematoxylin and Eosin (H&E) stained slides were examined, and reticulin staining was also conducted for a better assessment of fibrosis in hepatic tissues. All available information was meticulously documented in tables and charts. For data analysis, Microsoft Excel 2007 and Statistical Package for Social Sciences (SPSS) software version 16.0 for windows were used. Results: Majority of the patients 23 (47.91%) were between 1 year and 6 years of age. There was variation in the histopathological findings, with age-wise distribution of different changes in liver tissue documented. Reticulin-stained slides showed prominent fibrosis in liver tissue, which is associated with poor prognosis. The data indicated that there were an equal number of patients (50%) with histologically proven liver cirrhosis in the <1 year and 1-6 years age group. There were no cases of cirrhosis in the >6-12 years age group. Eight cases of liver fibrosis were observed, ranging from mild to severe, while the remaining 40 cases presented with no fibrosis. Among those with fibrosis, 2 cases (25%) were in the <1 year category, 5 (62.5%) cases were in the 1-6 years category, and 1 (12.5%) case was in the >6-12 years category. Conclusion: Fibrosis and cirrhosis were found to be more common in children aged 1-6 years compared to older children. Reticulin staining is an excellent method for confirming the presence of increased fibrosis in the liver, and these findings are very helpful for assessing prognosis and following-up with patients.